Thermally stimulated exoelectron emission from solid Xe: Electronic Processes in Cryocrystals - Khyzhniy, I.V.; Grigorashchenko, O.N.; Ponomaryov, A.N.; Savchenko, E.V.; Bondybey, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Thermally-stimulated emission of exoelectrons and photons from solid Xe pre-irradiated by low-energy electrons were studied. A high sensitivity of thermally-stimulated luminescence (TSL) and thermally-stimulated exoelectron emission (TSEE) to sample prehistory was demonstrated. It was shown that electron traps in unannealed samples are characterized by a much broader distribution of trap levels in comparison with annealed samples and their concentration exceeds in number that in annealed samples. Both phenomena, TSL and TSEE, were found to be triggered by release of electrons from the same kind of traps. The data obtained suggest a competition between two relaxation channels: charge recombination and electron transport terminated by TSL and TSEE. It was found that TSEE predominates at low temperatures while at higher temperatures TSL prevails. An additional relaxation channel, a photon-stimulated exoelectron emission from pre-irradiatedsolid Xe, was revealed.